Phenotypic analysis and genome sequence of Rhizopus oryzae strain Y5, the causal agent of tobacco pole rot - Li, Zhen; Shi, Cai-hua; Huang, Yang; Wang, Han-cheng; Li, Wen-hong; Cai, Liu-ti (Frontiers in Microbiology, 2023)
Rhizopus oryzae is a destructive pathogen that frequently causes tobacco pole rot in curing chambers. Phenotypic characterization of the pathogen was conducted to provide basic biological and pathological information using Biolog Phenotype MicroArray (PM). In addition, the Y5 strain of R. oryzae was sequenced using Illumina HiSeq and Pacific Biosciences (PacBio) technologies. Using PM plates 1–8, 758 growth conditions were tested. Results indicated that R. oryzae could metabolize 54.21% of tested carbon sources, 86.84% of nitrogen sources, 100% of sulfur sources, and 98.31% of phosphorus sources. About 37 carbon compounds, including D-xylose, N-acetyl-D-glucosamine, D-sorbitol, β-methyl-D-glucoside, D-galactose, L-arabinose, and D-cellobiose, significantly supported the growth of the pathogen. PM 3 indicated the active nitrogen sources, including Gly-Asn, Ala-Asp, Ala-Gln, and uric acid. PM 6–8 showed 285 different nitrogen pathways, indicating that different combinations of different amino acids support the growth of the pathogen. Genome sequencing results showed that the R. oryzae Y5 strain had raw data assembled into 2,271 Mbp with an N50 value of 10,563 bp. A genome sequence of 50.3 Mb was polished and assembled into 53 contigs with an N50 length of 1,785,794 bp, maximum contig length of 3,223,184 bp, and a sum of contig lengths of 51,182,778 bp. A total of 12,680 protein-coding genes were predicted using the Nonredundant, Gene Ontology, Clusters of Orthologous Groups, Kyoto Encyclopedia of Genes and Genomes, and SWISS-PROT databases. The genome sequence and annotation resources of R. oryzae provided a reference for studying its biological characteristics, trait-specific genes, pathogen-host interaction, pathogen evolution, and population genetic diversity. The phenomics and genome of R. oryzae will provide insights into microfungal biology, pathogen evolution, and the genetic diversity of epidemics.